Transforming piano tuition: A cross-arts approach inspired by “Peter and the Wolf” - Wu, Wei Chen; Turner, Ming; Yang, Chia-Han (Journal of Interdisciplinary Studies in Education, 2024)
This study explores the impact of interdisciplinary pedagogies combining music and other art forms on elementary piano students. Using action research, we assessed eight students and their parents through pre-, post-, and follow-up tests (June 2022–May 2023). The intervention incorporated story narratives, movement, music creation, and visual art, with data from field notes, diaries, video recordings, focus groups, and surveys. Qualitative data were analyzed through theoretical coding, and quantitative data via descriptive statistics. Results showed positive outcomes, particularly in addressing home practice challenges. This study underscores how interdisciplinary approaches reshape student attitudes, enhance learning outcomes in music education, and foster a sense of accomplishment